(untitled) - Kirst-Ashman, Karen Kay; Hull, Grafton H (Belmont, 2009)
Neal A. Newfield, Ph.D., LICSW (Giver) ; Includes bibliographical references (pages [585]-604) and indexes
Keywords: Social case work; Social service; Dịch vụ xã hội